“Clear vision, better schools”: The role of instructional leadership in enhancing service quality - Fadhli, Fadhli; Komariah, Aan; Satori, Djaman; Marwan, Marwan (Journal of Educational Management and Instruction (JEMIN), 2025)
Given the increasing demand for high-quality educational services, especially in developing regions, understanding the leadership factors that contribute to service enhancement is crucial. This study investigates the influence of instructional leadership on the quality of school services in vocational high schools, highlighting its significance in the broader context of educational improvement. The study specifically aims to examine how instructional leadership impacts various dimensions of school service quality, with a focus on vocational education settings in Bireuen Regency, Aceh, Indonesia. Employing a quantitative approach, data were collected from 80 vocational high school teachers and analyzed using Structural Equation Modeling (SEM). The findings reveal that the instructional leadership indicator most strongly associated with improved service quality is the leader’s orientation toward a clear vision and mission. This dimension significantly influences the ‘tangibility’ aspect of school services, indicating that visionary leadership is closely linked to improved physical facilities and resources, thereby shaping teachers’ perceptions of service quality. These results underscore the strategic role of leadership in creating an environment conducive to quality education. The study offers practical implications for policymakers and school administrators, advocating for leadership development programs that focus on vision-oriented management and sustained professional growth. Future studies are recommended to explore complementary variables such as school climate, teacher motivation, and institutional policies to build a more comprehensive model for enhancing school service quality.